Faktor-Faktor yang Memengaruhi Repurchase Intention pada Network Orchestrator X - Tedy Tedy Tedy; Abu Bakar Adni; Aloysius Evan Kristian; Iqbal Asyarf Lufty; Muhammad Faried Romdolni (Jurnal Manajemen, 2020)
Abstract The development of peer-to-peer lodging begins with the presence of Airbnb in 2008 which is connected in 192 countries and served 60 million travelers worldwide. The presence of Airbnb has led to several similar business models, namely the network orchestrator. In Indonesia, network orchestrator x appeared in 2015 with a business model similar to a hotel, but assets in the form of buildings and their contents are owned by partners/third people. Network orchestrator x provides an application system integrated with a smartphone. In this study the questionnaire was distributed to 401 respondents and the number that could be used was 226 questionnaires. This research was conducted by adding two variables to the existing research model which is tangible and intangible variables. Based on the research, factors that significantly affect customer satisfaction are product performance risk, room and bathroom size, staff's helpfulness, accuracy of service, personal attention, and customer satisfaction also significantly influence repurchase intention.